2006
DOI: 10.1002/nau.20364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with urethral retro‐resistance pressure measurement: A prospective pre‐ and postoperative evaluation in women with stress urinary incontinence

Abstract: Preoperative URP does not correlate with SUI in all women, has no predictive value, and does not correlate with the outcome of anti-incontinence surgery. However, there seems to be an association with biomechanical factors such as obesity, which may open up a new area of application for URP measurement in urogynecologic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…15,16 Urodynamic data from Bai et al indicated that mean flow rate was significantly lower in obese patients than in nonobese patients. Tunn et al 17 found an association where increased urethral resistance pressure correlated with increased BMI. Although obese women have historically been shown to have a decrease in flow rate before surgery, this study suggests that this does not negatively affect their ability to pass a postoperative voiding trial.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 Urodynamic data from Bai et al indicated that mean flow rate was significantly lower in obese patients than in nonobese patients. Tunn et al 17 found an association where increased urethral resistance pressure correlated with increased BMI. Although obese women have historically been shown to have a decrease in flow rate before surgery, this study suggests that this does not negatively affect their ability to pass a postoperative voiding trial.…”
Section: Discussionmentioning
confidence: 98%
“…Although used as standard diagnostic tools, a significant disagreement between EMG and voiding cystography for a positive diagnosis of detrusorÁ external sphincter dysfunction could be demonstrated [10]. The urethal pressure profile is not well standardized and is influenced by several factors, so its clinical value is questionable [11,12]. Another way to assess pelvic floor muscle strength and coordination is by vaginal palpation or measurement of vaginal contraction strength by perineometry [13].…”
Section: Discussionmentioning
confidence: 99%
“…Der aus 3 Einzelmessungen erhaltene Mittelwert gibt, entsprechend der Einteilung nach Slack et al [16], die Wahrscheinlichkeit für eine Belastungsharninkontinenz an. Digesu et al [6] und Tunn et al [21] konnten diese Korrelation insbesondere nach operativer Korrektur der Belastungsharninkontinenz nicht bestätigen. Somit konnte sich die retrograde Widerstandsmessung im klinischen Alltag bisher nicht etablieren.…”
Section: Neues Zur Diagnostikunclassified